Sustainability in construction:: an assessment of the energy life cycle and of CO2 emissions for social housing facades - Caldas, Lucas Rosse; Sposto, Rosa Maria; Pires, Armando Caldeira; Paulsen, Jacob Silva (Sustainability in Debate, 2016)
As a consequence of the debate about the environmental impacts of construction activities, current research has started to focus on the selection of materials and on construction systems using sustainability criteria. In this context, this study aimed at using two environmental indicators, energy consumption and CO2 emissions, to evaluate four FACADE systems for social housing in Brazil: light steel framing, on site concrete molded wall, structural concrete blocks and structural ceramic blocks. The methodology included a Energy Life Cycle Assessment (ELCA) and the CO2 Emissions Life Cycle Assessment (LCCO2 ELCA) in the phases of extraction, processing and maintenance of the systems. Based on the two selected indicators, the concrete wall system achieved the lowest energy consumption rate, 189,4 MJ/m², and the lowest level of CO2 emissions, 28,6 kgCO2/m², therefore proving to be the most sustainable system for social housing purposes.